Phosphine‐Catalyzed (3+2) Annulation of Isoindigos with Allenes: Enantioselective Formation of Two Vicinal Quaternary Stereogenic Centers. Issue 19 (27th February 2019) - Chan, Wai‐Lun; Tang, Xiaodong; Zhang, Fuhao; Quek, Glenn; Mei, Guang‐Jian; Lu, Yixin
Abstract: Construction of contiguous all‐carbon quaternary stereogenic centers is a long‐standing challenge in synthetic organic chemistry. In this report, a phosphine‐catalyzed enantioselective (3+2) annulation reaction between allenes and isoindigos, containing either two identical or different oxindole moieties, is introduced as a powerful strategy for the construction of spirocyclic bisindoline alkaloid core structures. The reported reactions feature high chemical yields, excellent enantioselectivities, and very good regioselectivities, and are highly useful for creating structurally challenging bisindoline natural products. Abstract : Strategic move : The phosphine‐catalyzed enantioselective (3+2) annulation reaction between allenes and isoindigos is introduced as a powerful strategy for the construction of structural motifs containing two vicinal quaternary stereogenic centers. The reactions feature high yields, enantioselectivities, and regioselectivities, and are highly useful for creating structurally challenging hexahydropyrroloindoles (HPIs).